Analyzing the Current State of Ukrainian Restaurant Business and Prospects for Development in the Context of the COVID-19 Pandemic - Kuchechuk Larysa V. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The article is aimed at analyzing the current state of the restaurant economy of Ukraine and determining prospects for its development in the context of the COVID-19 pandemic. This study analyzes the impact of the COVID-19 pandemic on the quantitative composition of the national restaurant services market. A significant reduction in the number of establishments in 2020, as well as a significant decrease in sales compared to 2019, are identified. The regions with the biggest number of establishments engaged in restaurant business are defined. The specific structure of establishments of the domestic restaurant sphere is considered. The quantitative composition of restaurant establishments by forms of entrepreneurial activity is analyzed. It is identified that the restaurant market of Ukraine became one of the most affected sectors of the economy during the COVID-19 pandemic. As a result of the research, the main prospects for the development of the restaurant economy market of Ukraine in modern crisis conditions are determined. Among them the following are allocated: development of mobile applications with a wide range of functions and order tracking; increasing online sales by introducing advertising tools such as promoting own website on the Google search network and using contextual advertising; banner advertising and remarketing; support of pages in social networks and cooperation with bloggers, journalists, critics, opinion leaders. Promising directions of development are also identified: opening or improving the establishment’s summer playground, organizing a smooth transfer of orders through the issue window, own order delivery service. It is noted that the reduction of rent rates on premises under the influence of a pandemic and an increase in the number of franchising establishments have a positive impact on the resumption of the restaurant services market.